Afternoon on the Amazon - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 1995)
Eight-year-old Jack, his seven-year-old sister, Annie, and Peanut the mouse ride in a tree house to the Amazon rain forests, where they encounter giant ants, flesh-eating piranhas, hungry crocodiles, and wild jaguars.
Book Links (A.L.A.), July 2004.
2.6
K-3
510L
M
Keywords: Rain forests -- Fiction; Rain forest animals -- Fiction; Adventure and adventurers -- Fiction; Tree houses -- Fiction; Adventure fiction; Amazon River Valley -- Fiction